ANALISIS PENGARUH TINGKAT LEVERAGE TERHADAP KINERJA PERUSAHAAN (Studi pada Perusahaan Food and Beverage yang Terdaftar di BEI Tahun 2011-2013) - Luluk M Ifada; Nayirotul Inayah (STIE Pelita Nusantara Semarang, 2017)
This study aims to determine the direction of empirical about the influence of leverage level on company performance. By using sample of companies engaged in food and beverages listed on the Indonesia Stock Exchange during 2011-2013. Data were analyzed by using multiple regression technique. Secondary data is obtained from Indonesi Capital Market Directory (ICMD) and annual reporting company taken samples for three years, issued by BEI. Two variables were used in this research to analyze leverage level: Debt Ratio (DR) and Debt to Equity Ratio (DER), and Return on Equity (ROE) to analyze company performance. The results of this study indicate that the use of debt affects the performance of the company, so the company should consider the level of leverage